Establishing Genetic Relationships between the Takidani Pluton and Two Large Silicic Eruptions in the Northern Japan Alps. (6th October 2021) - Hartung, Eva; Caricchi, Luca; Floess, David; Wallis, Simon; Harayama, Satoru
Abstract: The Takidani pluton (1·1–1·6 Ma) represents a shallow magmatic reservoir at the base of an exhumed caldera floor. The deposits of two large caldera-forming eruptions, the Nyukawa Pyroclastic Flow Deposit (1·76 Ma; crystal-rich dacite) and the Chayano Tuff and Ebisutoge Pyroclastic Deposits (1·75 Ma; a sequence of crystal-poor rhyolite), are distributed concentrically around the pluton. We use major and trace element chemistry of whole-rock, glass and minerals to show that (1) the crystal-rich dacite (>400 km 3 DRE; dense rock equivalent) is the erupted portion of a shallow mush zone constituting the Takidani pluton and (2) the crystal-poor rhyolite (>100 km 3 DRE) was extracted from a deeper part of this vertically extended magmatic plumbing system. Whole-rock geochemistry indicates that the Nyukawa and Takidani compositions were produced dominantly through crystal fractionation of amphibole, pyroxene and plagioclase in the mid to lower crust and subsequently emplaced in the upper crust prior to eruption and solidification, respectively. The crystal-poor Chayano–Ebisutoge rhyolite (>100 km 3 DRE) is compositionally distinct from the Nyukawa and Takidani magmas and its generation is associated with a substantial contribution of crustal melts. However, plagioclase and orthopyroxene textures and chemistry provide strong evidence that the ascending rhyolite percolated through the upper Takidani–Nyukawa mush zone prior to eruption. Overgrowth of 'rhyolitic plagioclase' on 'xenocrystic dacitic plagioclase' typical of the Takidani–Nyukawa magmas indicates that the extraction and accumulation of the rhyolitic melts could have occurred in less than 10 kyr (i.e. the time between eruptions) prior to eruption, providing maximum timescales for pre-eruption storage. Overall, our findings show a progressive growth and thermal maturation of a vertically extended magmatic plumbing system over hundreds of thousands of years and imply that large volcanic eruptions can occur in relatively short succession without dramatic changes in the plumbing system, thus complicating the identification of signs of an impending large eruption.